Punk teacher education: Finding ways to interrupt the harmful effects of teacher accountabilities. Issue 1 (May 2023) - Vass, Greg
In recent years a suite of policies and practices that are strongly influenced by efforts to make the work of educators and education providers more accountable, have had a powerful impact across the sector in settings such as Australia. In part, this goes some way to explaining why many working in the teaching profession report being dissatisfied with their role in education, and significant numbers leave the profession within the initial 5 years in Australia. Both in this context and beyond, there is a growing chorus of voices that encourage finding ways to push back and interrupt the impacts of accountability initiatives in education. Teacher education is itself one of the contexts in which this contestation is playing out, and whether it be voiced in terms of reimagining, revolutionising, or reclaiming education, the core sentiment can be interpreted as a type of call to arms for those working with educators. In this paper, I will make the case that punk can productively contribute to efforts responding to the influences of dominant culture in education. Punk in this usage can be thought of as social practices that generate cultural resources that can be utilised to question and critique dominant culture.